Bridging the Gap: Empowering Lecturers through Effective Quality Management Practices in Higher Education - Lusy Tunik Muharlisiani; Kaswadi Kaswadi; Widyatmike Gede Mulawarman; Nugrahini Susantinah Wisnujati; Pratiwi Dwi Karjati; Azlina Idris (AL-ISHLAH: Jurnal Pendidikan, 2024)
This paper aims to identify the factors affecting self-esteem and confidence among educators and how these factors influence their teaching effectiveness. The study employs a qualitative approach to explore self-esteem and lecturer performance. Data were collected through interviews and analyzed both concurrently and post-collection to ensure comprehensive understanding and immediate adjustment of interview questions as needed. The findings revealed that lecturers with low self-esteem and confidence often struggle with managing emotions and maintaining a balanced psychological state. The most significant contributor to low confidence was found to be an individual's personality, specifically their ability to control emotions. The study demonstrated that the primary driver of self-esteem is not stress, but an imbalance in mental processes. Additionally, this research developed a scale to measure self-esteem using two dimensions: acute fatigue and cognitive distortion. For confidence, the scale includes the dimensions of certainty and the reduction of certainty. These scales provide valuable tools for assessing and addressing issues of self-esteem and confidence among educators, ultimately contributing to improved teaching effectiveness and educational quality. The study contributes to the existing literature by highlighting the role of personality traits and emotional regulation in lecturer burnout and self-esteem, emphasizing the need for a holistic approach in addressing these issues in higher education.